Pengembangan Sistem E-Commerce Berbasis Web dengan Optimalisasi Database untuk Penjualan Produk UMKM - Rizky, Dinnar; Zulfikar, Fiqih (PT Jurnal Cendekia Indonesia, 2025)
MSMEs are a crucial sector for maintaining economic growth, but they still face challenges in online marketing and inefficient transaction data management. Previous research has shown that e-commerce can increase MSME revenue and competitiveness, but system performance is often hampered by suboptimal database design. This research aims to create a web-based e-commerce system by applying database optimization techniques to make transaction processes and data management more efficient. The Waterfall method was used in developing this system, encompassing requirements analysis, design, implementation, and testing. The database optimization process was carried out by creating indexing, improving query structures, and normalizing tables based on previous research on database optimization in MySQL and other DBMSs. Test results showed that the implementation of indexing and query optimization significantly reduced execution time for product searches and transactions compared to the initial design. The successfully created e-commerce system was able to support MSME sales processes more quickly, structured, and efficiently. Thus, this research contributes to the implementation of a system that not only focuses on e-commerce functions but also improves database performance as a crucial part of MSME digital transformation.